Analisis Pengaruh Anggaran Pendapatan dan Belanja Negara Terhadap Pertumbuhan Ekonomi di Indonesia - Aisyah Khairani Lubis; Syarifah Khairatun Hisan; Ahmad Wahyudi Zein (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The State Revenue and Expenditure Budget (APBN) is a fundamental fiscal policy instrument for realizing national development and public welfare. This study aims to analyze the correlation between APBN management and Indonesia’s economic growth, focusing on the effectiveness of government spending and oversight of budget misappropriations. Based on the 2023 audit report by the Supreme Audit Agency (BPK), financial losses due to APBN mismanagement reached IDR 8.2 trillion, highlighting the weakness in financial oversight and transparency. Using a descriptive qualitative approach, this study explores the significance of budget efficiency and the implementation of APBN’s fiscal functions in supporting macroeconomic stability. The findings suggest that government spending significantly influences economic growth, yet its effectiveness is heavily dependent on robust monitoring systems and sound fiscal strategies. Therefore, strengthening fiscal transparency and supervision is crucial to prevent state losses and promote equitable development.